Exploring Consumer Psychology in Marketing Management: A Strategic Perspective through Descriptive Inquiry and Literature Review - Mandung, Fitriani; Sahari, S.; Razak, Sitti Rahmi (Manunggal Halim Jaya, 2024)
This study delves into the intricate dynamics of consumer psychology within the realm of marketing management, aiming to provide valuable insights for marketers and researchers alike. Employing a descriptive inquiry methodology, the research explores various factors influencing consumer behavior, including internal determinants, cognitive processes, and external influences. Through a systematic literature review and thematic analysis, the study elucidates the critical role of brand equity in driving consumer choice and purchase behavior. Additionally, the research highlights the significance of pricing strategies, cognitive biases, and impulse buying behavior in shaping consumer preferences and decisions. The findings underscore the importance of understanding the interplay between situational cues, mood states, and individual traits in driving impulse purchases, offering actionable insights for marketers seeking to capitalize on spontaneous buying opportunities. Moreover, the study identifies emerging trends such as the influence of social media, cultural values, and experiential marketing on consumer behavior, paving the way for further research in this dynamic field. Overall, this research contributes to the ongoing discourse on consumer psychology and offers practical implications for marketers aiming to enhance brand engagement, foster customer loyalty, and drive sustainable business growth.